Estruturas burocráticas e capacidade de ação: construindo burocracias autônomas e inseridas no Brasil - Godoy, André Luz de (2010)
This study aims to verify the influence of bureaucratic structures of public institutions in their execution capacity. For this purpose, this study has as its study object the human resource structure of the Brazilian Hea1th Care Ministry and of the Oswaldo Cruz Foundation. lt was analyzed the impact of their human resources structures in the development of their actions in the 'Programa Mais Saúde: Direito de Todos', specifically in the Health Industrial Complex Axis. Data was collected through bibliographical, documental and field research. Bibliographical and documental data were collected through reports on the program and on the participant institutions. The field research was made through semi-structured interviews with project managers, ex-managers, and representatives of companies associations, banks and development agencies. The results stress the need of coexistence of flexible and traditional recruitment mechanisms. Even though deficit of meritocratic weberian careers remain perceptible in Brazil, it is necessary to invest in the flexibility of individualist career models, since both dimensions give feedback to each other and, when equilibrated, contribute to consolidate an embedded and autonomous State.